PENGARUH PEMAHAMAN SEJARAH PERGERAKAN NASIONAL DAN SIKAP NASIONALISME TERHADAP WAWASAN KEBANGSAAN PADA SISWA KELAS XI IPS DI SMA BATIK 1 SURAKARTA TAHUN 2015/2016 - Akbar, Indah Rahmawati; Suryani, Nunuk; Isawati, Isawati (Candi, 2017)
The purpose of this research are: 1) to determine the effect comprehension of national movement history with nationality concept in class XI IPS SMA Batik 1 Surakarta, 2) to determine the effect attitude of nationalism with nationality concept in class XI IPS SMA Batik 1 Surakarta, 3) to determine the effect comprehension of national movement history and attitude of nationalism with nationality concept in class XI IPS SMA Batik 1 Surakarta.This research is descriptive quantitative by draw conclusion through statistical analysis. The population of research were all student of class XI IPS SMA Batik 1 surakarta. The sample consisted of 125 students taken using simple randong sampling technique. The data need was obtained through test and questionare. The test and questionare was tried out first and tasted for its validity and reliability. The tecnique of analizing data used was a multiple linear regresion analysis, F-, t-, R2-test, and relative and effective contribution.The conclusion of this study were: 1) There is a significant and positive effect comprehension of nationality movement history with nationality concept in class XI IPS SMA Batik 1 Surakarta. This is based on multiple linear regresion analysis (t test) showing that tstatistic>ttable, 2.069>1.657 and the significance value 0.041<0.05 with the relative contribution of 8.93% and effective contribution of 3.46%. 2) There is a significant and positive effect attitude of nationalism with nationality concept in class XI IPS SMA Batik 1 Surakarta. This is based on multiple linear regresion analysis (t test) showing that tstatistic>ttable, 8.137>1.657 and significance value 0.000<0.05 with relative contribution 91.11% and effective contribution of 35.26%. 3) There is a positive and significant effect comprehension of national movement history and attitude of nationalism along with nationality concept in class XI IPS SMA Batik 1 Surakarta. This is based on linear regresiona analysis (F test) known that Fstatistic>Ftable, is 38.504>3.070 and significance value 0.000<0.05. The coefficient of determination (R2) of 0.387 indicate that comprehension of national movement history and attitude of nationalism with nationality concept in class XI IPS SMA Batik 1 Surakarta year 2015/2016 affected 38.75, while the rest was affected by other variables.